The Legal Force of Article 1977 of the Indonesian Civil Code Regarding Ownership of Unregistered Movable Property - Camelia, Noer Dini; Rifai, Achmad; Heryanti, Febrina; Lutfiadi, Lutfiadi; Hanayanti, Citra Siwi (Jurnal Ilmu Hukum Kyadiren, 2026)
Technological and socio-economic developments have generated significant challenges for the application of Article 1977 of the Indonesian Civil Code (Burgerlijk Wetboek/BW), which governs ownership of unnamed movable property. Normatively, this provision stipulates that possession is deemed equivalent to ownership. However, in practice, difficulties arise in relation to modern electronic devices such as mobile phones and laptops, which can be uniquely identified through IMEI codes or serial numbers. This study examines the binding force of Article 1977 of the Civil Code, explores the legal issues associated with the ownership of unnamed movable property, and evaluates the provision’s relevance within the contemporary socio-economic and technological context. The research employs a normative juridical approach, supported by doctrinal analysis, statutory interpretation, and review of empirical literature on movable property ownership. Findings reveal that, although Article 1977 continues to provide formal legal certainty, it fails to adequately address technological advancements. Accordingly, the integration of digital identification mechanisms is essential to ensure substantive justice and safeguard property rights.